The Lentiviral System Construction for Highly Expressed Porcine Stearoyl‐CoA Desaturase‐1 and Functional Characterization in Stably Transduced Porcine Swine Kidney Cells. Issue 10 (27th December 2018) - Hwang, Jinhee; Singh, Neetu; Long, Charles; Smith, Stephen B.
Abstract: The most highly regulated and abundant fatty acid in animal tissue is oleic acid (18:1n9). Oleic acid is synthesized by the Δ9 desaturase, stearoyl‐CoA desaturase‐1 ( SCD1 ), which is responsible for the synthesis of the putative cytokine palmitoleic acid (16:1n7) and 18:2 cis ‐9, trans ‐11 conjugated linoleic acid. Owing to the importance of SCD1 in lipid metabolism, we generated porcine swine kidney (SK6) transgenic cell lines for sustained overexpression or knockdown of porcine stearoyl‐CoA desaturase‐1 ( pSCD1 ) in an inducible manner by utilizing a lentiviral expression system. We successfully validated these cell culture models for expression and functionality of pSCD1 by documenting that the pSCD ‐transduced cells overexpressed pSCD1 protein and mRNA. Additionally, the pSCD1 ‐transduced cells increased the conversion of palmitate (16:0) to palmitoleic acid nearly fourfold. The lentiviral vectors utilized in this study can be further used to generate transgenic animals to document the effects of the overexpression of SCD1 on obesity and steatosis.